The Effectiveness of Digitizing Tax Administration to Reduce the Compliance Cost of Taxpayers of Micro, Small, and Medium Enterprises (MSMEs) - Scheilla Aprilia Murnidayanti; Titi Muswati Putranti (Jurnal Public Policy, 2023)
MSMEs are a growing and vital sector for the country's economy. However, until now, MSMEs taxpayer compliance is still low. DGT then digitized tax administration with the aim of reducing taxpayer compliance costs for MSMEs taxpayers. This paper analyzes the effectiveness of digitizing tax administration in reducing MSMEs taxpayer compliance costs and DGT's steps to reduce MSMEs taxpayer compliance costs. The method used in this study is qualitative with a literature study approach. Secondary data was obtained from various library sources, including books, encyclopedias, dictionaries, journals, documents, magazines, etc. The study results show that the digitization of tax administration in Indonesia has not reduced the cost of taxpayer compliance for MSMEs taxpayers. In addition, other factors that can influence MSMEs taxpayer compliance include knowledge, mediation, perceptions of fairness, and so on. DGT has simplified the tax system and digitized tax administration to reduce tax compliance costs. The originality of this research is in analyzing the relationship between the digitization of tax administration and tax compliance costs for MSMEs.